Evaluation of the glycemic effect of Ceratonia siliqua pods (Carob) on a streptozotocin-nicotinamide induced diabetic rat model - Qasem, Mousa Abdullah; Noordin, Mohamed Ibrahim; Arya, Aditya; Alsalahi, Abdulsamad; Jayash, Soher Nagi (PeerJ, 2018)
Background. Ceratonia siliqua pods (carob) have been nominated to control the high blood glucose of diabetics. In Yemen, however, its antihyperglycemic activity has not been yet assessed. Thus, this study evaluated the in vitro inhibitory effect of the methanolic extract of carob pods β-cells (RIN-5F). Acute oral toxicity of carob was conducted on a total of 18 male and 18 female Sprague-Dawley (SD) rats, which were subdivided into three groups (nD6), namely: high and low dose carob-treated (CS5000 and CS2000, respectively) as well as the normal control (NC) receiving a single oral dose of 5,000 mg kg -1 carob, 2,000 mg kg -1 carob and 5mLkg -1 distilled water for 14 days, respectively. Alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase, total bilirubin, creatinine and urea were assessed. Livers and kidneys were harvested for histopathology. In vitro inhibitory effect against α-amylase and α-glucosidase was evaluated. In vivo glycemic activity was conducted on 24 male SD rats which were previously intraperitoneally injected with 55 mg kg -1 streptozotocin (STZ) followed by 210 mg kg -1 nicotinamide to induce type 2 diabetes mellitus. An extra non-injected group (n D 6) was added as a normal control (NC). The injected-rats were divided into four groups (n D 6), namely: diabetic control (D0), 5 mg kg -1 glibenclamide-treated diabetic (GD), 500 mg kg -1 carob-treated diabetic (CS500) and 1,000 mg kg -1 carob-treated diabetic (CS1000). All groups received a single oral daily dose of their treatment for 4 weeks. Body weight, fasting blood glucose (FBG), oral glucose tolerance test, biochemistry, insulin and hemostatic model assessment were assessed. Pancreases was harvested for histopathology. Results. Carob demonstrated a FRAP value of 3191.67 ± 54.34 mmoL Fe ++ and IC 50 of DPPH of 11.23 ± 0.47 mg mL -1 . In vitro, carob was non-toxic on hepatocytes and pancreatic β-cells. In acute oral toxicity, liver and kidney functions and their histological sections showed no abnormalities. Carob exerted an in vitro inhibitory effect against α-amylase and α-glucosidase with IC 50 of 92.99 ± 0.22 and 97.13 ± 4.11 mg mL -1 , respectively. In diabetic induced rats, FBG of CS1000 was significantly less than diabetic control. Histological pancreatic sections of CS1000 showed less destruction of β-cells than CS500 and diabetic control. Conclusion. Carob pod did not cause acute systemic toxicity and showed in vitro antioxidant effects. On the other hand, inhibiting α-amylase and α-glucosidase was evident. Interestingly, a high dose of carob exhibits an in vivo antihyperglycemic activity and warrants further in-depth study to identify the potential carob extract composition.